STUDY THE EFFECT OF ETHANOLIC EXTRACT OF ( MATRICARIA RECUTITA AND GLYCYRRHRZA GLABRA) COMPARED WITH CIMETIDINEE IN TREATING GASTRIC ULCERATION IN RABBITS INDUCED BY ASPIRIN - HassanT; Huda K.Khasaf; Abdulrhazzak N.Khudeir (Basrah Journal of Veterinary Research)
This study aimed to evaluate the effect of the drenching ethanolic extract of Chamomile and licorice at a dose of (100 mg/kg and 250 mg/kg ) respectively in treating gastric ulcer induced by aspirin in rabbits. The study included the effect of drenching the ethanolic extract of both plants on the gastric ulcer index ,gastric juice pH, and volume of gastric fluid as well as curative ratio. Results revealed that treatment with cemitidine and Chamomile or licorice or their combination was associated with significant(p